Forms and drivers of annual streamflow variability in the headwaters of Canadian Prairies during the 20th century - Nazemi, Ali; Wheater, Howard S.; Chun, Kwok Pan; Bonsal, Barrie; Mekonnen, Muluneh (Hydrological processes, 2017)
Headwater streamflows in the Rocky Mountain foothills are the key to water availability in the Canadian Prairies. Headwater characteristics, however, have been and continue to be subject to major variability and change. Here, we identify various forms of change in the annual mean streamflow and timing of the annual peak and attempt to distinguish between the effects of multiple drivers using a generalized regression scheme. Our investigation shows that the Pacific Decadal Oscillation (PDO) is the main driver of significant monotonic trends and shifts in the central tendency of annual mean streamflow in major headwaters. In parallel, the cumulative effects of non‐PDO climatic drivers and human‐induced land use and land management are the main causes of significant variations in the timing of the annual peak. Additional analyses show that time sequences with significant trends in annual mean streamflow and timing of the annual peak coincide with those that show significant trends in the PDO or non‐PDO component of the air temperature, respectively. The natural streamflow characteristics are substantially perturbed by anthropogenic river flow regulation, depending on the form of change and/or the level of regulation. Evidence suggests that the general tendency of human regulation is to alleviate the severity of above‐ and below‐average streamflow conditions; however, it may also intensify the variability in natural streamflow characteristics during drier years and/or those with earlier annual peak timing. These are circumstances to which the regional water resource system is vulnerable. Our findings are important for the provision of effective regional water resource management in the Canadian Prairies and contribute to a better understanding of the complex interactions between natural and anthropogenic drivers in coupled human–water systems.